AUTHORITY OF MILITARY POLICE INVESTIGATORS REGARDING CRIMINAL ACTS OF CORRUPTION ACCORDING TO LAW NUMBER 31 OF 1997 CONCERNING MILITARY JUSTICE - Abdul Hayy Nasution, (International Journal of Social Science, 2024)
The background to this research is the investigation carried out by investigators within the scope of Military Justice with its implementation, and the role of the Military Police (POM) which coordinates with the Corruption Eradication Commission (KPK) as the front guard in eradicating Corruption Crimes. The problem in this research is the authority of Military Police Investigators (POM) regarding Corruption Crimes according to the Military Justice Law, as well as how the Military Police Investigators' (POM) Authority is implemented for Corruption Crimes according to the Military Justice Law. This research uses sociological jurisprudence. The sociological juridical approach is a research method carried out to obtain primary data and find the truth using inductive thinking methods and corresponding truth criteria and the facts used to carry out the induction process and correspondent truth testing are up-to-date facts. The way this sociological juridical method works in this research is from the results of collecting and discovering data and information through literature study of the basic assumptions and presumptions used in answering the problems in this research. The purpose of this research is to find out the authority of Military Police Investigators regarding Corruption Crimes according to the Military Justice Law, as well as how the authority of Military Police Investigators is implemented regarding Corruption Crimes according to the Military Justice Law